Developing international EFL/ESL scholarly writers - Butler, Donna (Studies in second and foreign language education ;, 2015)
This text provides a research-based approach for developing EFL/ESL writers in disciplinary/professional context. Research results disclose the interplay among strategies, skills, quality assessment, and stages (a) defining strategic competence for participants, and (b) acting as catalyst for increasing writing proficiency in a legal research paper or article.